Further observations on nematodes associated with rice in Côte d'Ivoire, The Gambia, Guinea and Togo - Coyne, Danny L.; Hunt, D.J.; Plowright, R.A.; Darboe, M.L.K. (2000)
Eighty six rice fields in Côte d'Ivoire, 21 in The Gambia, 56 in Guinea and 21 in Togo were surveyed for plant parasitic nematodes. Ninety-nine species from 34 genera were recovered from rainfed upland, hydromorphic and lowland rice ecosystems in the forest and savannah agroecological zones. Helicotylenchus, represented by 11 species, was the most prevalent genus in Côte d'Ivoire, Guinea and Togo. In the forest zone, in Côte d'Ivoire and Guinea, Xiphinema was highly prevalent. A total of 23 species of Xiphinema were associated with rice including a potential four new species. Peltamigratus nigeriensis occurred frequently in upland fields on the Danyi-Apeyeme plateau in Togo. Poor rice development was associated with the presence of heteroderid spp. in Côte d'Ivoire, Guinea and Togo and population densities of 200 Pratylenchus zeae per 5 g root in Togo. Species prevalence and their population densities were low in The Gambia, where crop development was at an early stage. The lowland rice weeds Oryza longistaminata and Scorpius [?Scorpiurus] sp. supported higher population densities of Xiphinema bergeri than rice in Guinea.